Evolutionary expansion and divergence in the ZNF91 subfamily of primate-specific zinc finger genes - Hamilton, Aaron T.; Huntley, Stuart; Tran-Gyamfi, Mary; Baggott, Daniel M.; Gordon, Laurie; Stubbs, Lisa (Genome Research, 2006)
Most genes are conserved in mammals, but certain gene families have acquired large numbers of lineage-specific loci through repeated rounds of gene duplication, divergence, and loss that have continued in each mammalian group. One such family encodes KRAB-zinc finger (KRAB-ZNF) proteins, which function as transcriptional repressors. One particular subfamily of KRAB-ZNF genes, including ZNF91, has expanded specifically in primates to comprise more than 110 loci in the human genome. Genes of the ZNF91 subfamily reside in large gene clusters near centromeric regions of human chromosomes 19 and 7 with smaller clusters or isolated copies in other locations. Phylogenetic analysis indicates that many of these genes arose before the split between the New and Old World monkeys, but the ZNF91 subfamily has continued to expand and diversify throughout the evolution of apes and humans. Paralogous loci are distinguished by divergence within their zinc finger arrays, indicating selection for proteins with different regulatory targets. In addition, many loci produce multiple alternatively spliced transcripts encoding proteins that may serve separate and perhaps even opposing regulatory roles because of the modular motif structure of KRAB-ZNF genes. The tissue-specific expression patterns and rapid structural divergence of ZNF91 subfamily genes suggest a role in determining gene expression differences between species and the evolution of novel primate traits.